Modeling and Reconstruction of State Variables for Low-Level Control of Soft Pneumatic Actuators - Ibrahim, Serhat; Krause, Jan Christoph; Olbrich, Alexander; Raatz, Annika (Frontiers in Robotics and AI, 2021)
To further advance closed-loop control for soft robotics, suitable sensor and model strategies have to be investigated. Although there are many flexible and soft sensors available, the integration into the actuator and the use in a control loop is still challenging. Therefore, a model of state variables for closed-loop low-level control for a fiber-reinforced actuator using pressure and orientation measurement is investigated. To do so, the integration of an inertial measurement unit and geometric modelling of actuator is presented. The piece-wise constant curvature approach is used to describe the actuator's shape and deformation variables. For low-level control, the chamber's lengths are reconstructed from bending angles with a geometrical model and the identified material characteristics. For parameter identification and model validation, data from a camera tracking system is analyzed. Then, a closed-loop control of pressure and chambers' length of the actuator is investigated. It will be shown, that the reconstruction model is suitable for estimating the state variables of the actuator. In addition, the use of the inertial measuring unit will demonstrate a cost-effective and compact sensor for soft pneumatic actuators.